Thermodynamics of strain-induced crystallization in filled natural rubber under uni- and biaxial loadings, Part II: Physically-based constitutive theory. (February 2022) - Khiêm, V.N.; Le Cam, J.-B.; Charlès, S.; Itskov, M.
Abstract: To understand thoroughly the strain-induced crystallization in natural rubbers, conventional mechanical measurements are inadequate because they only provide a macroscopic relation between stress and strain. In this second part, a physically-based constitutive model for filled natural rubbers is coupled with the infrared thermography-based quantitative surface calorimetry (Part I) to shed new light on multiaxiality of strain-induced crystallization. In contrast to previous works, the kinetics of phase transition outside thermodynamic equilibrium is discussed. By introducing only two additional parameters (compared to the equilibrium crystallization theory), underlying mechanisms of nonequilibrium strain-induced crystallization can be well interpreted. To capture multiaxiality of strain-induced crystallinity, the analytical network-averaging is utilized for the calculation of kinematic internal variables. Model predictions are then compared with comprehensive testing data (Part I) and demonstrate good agreement with these experiments.